1991
DOI: 10.2307/3869301
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of the Plastid Protein Import Apparatus

Abstract: Plastid development involves the programmed accumulation of proteins. Most plastid proteins are synthesized in the cytosol and imported into the organelle by an envelope-based protein import apparatus. Previous studies have shown that developmental rates of protein accumylation correspond to mRNA levels. Here, we examined the relationship between plastid development and the activity of the protein import apparatus. Developing plastids, primarily from wheat leaves, were analyzed for their protein import capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
25
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 9 publications
5
25
0
Order By: Relevance
“…In almost all cases studied, the precursor proteins appeared to be continuously imported into the organelles (8)(9)(10). Although various plastid types may exhibit different transport competences for certain nuclearencoded plastid precursor proteins, as discussed previously (11)(12)(13), none of these polypeptides could be detected in vivo. In the present paper, however, the nuclear-encoded key enzyme of chlorophyll biosynthesis in higher plants, the lightdependent NADPH:protochlorophyllide (Pchlide) oxidoreductase (POR; EC 1.3.1.33) (14,15), has been shown to accumulate in its precursor form, pPORA, in vivo. pPORA's translocation across the plastid envelope is regulated through its substrate, Pchlide (16,17).…”
mentioning
confidence: 94%
“…In almost all cases studied, the precursor proteins appeared to be continuously imported into the organelles (8)(9)(10). Although various plastid types may exhibit different transport competences for certain nuclearencoded plastid precursor proteins, as discussed previously (11)(12)(13), none of these polypeptides could be detected in vivo. In the present paper, however, the nuclear-encoded key enzyme of chlorophyll biosynthesis in higher plants, the lightdependent NADPH:protochlorophyllide (Pchlide) oxidoreductase (POR; EC 1.3.1.33) (14,15), has been shown to accumulate in its precursor form, pPORA, in vivo. pPORA's translocation across the plastid envelope is regulated through its substrate, Pchlide (16,17).…”
mentioning
confidence: 94%
“…The third identified component, Ptc52, displays similarity to three, at first glance, quite unrelated proteins: the lethal leaf spot protein Lls1 (37), Tic55 (38), and the recently identified chlorophyllide a oxygenase (Cao) (19) (Fig. 3).…”
Section: The Ptc Complex Contains Pchlide and A Putative Pchlide A Oxmentioning
confidence: 99%
“…Jarvis et al (18) demonstrated that ''twin components'' of the same regulatory GTP-binding protein, Toc34 and Toc33, are differentially expressed during plant development. In 1991, Dahlin and Cline (19) observed that protein import is determined by developmental fate and age of the plant, implying a rather flexible nature of the responsible import machinery.…”
mentioning
confidence: 99%
“…Indications of such mechanisms in action were observed, e.g. during the preferential in vitro import of proteins into chloroplasts versus leucoplasts (19), for "younger" versus "older" plastids (20), or plastids of nitrogen-fixing versus nonfixing nodules (21). Toc75-encoding mRNA levels, the outer envelope channel protein, also change in a tissue-specific manner (leaf versus roots) (16).…”
mentioning
confidence: 99%